Generalized Moments of Sample Extremes of Order Statistics from Discrete Uniform Distribution (Asian Journal of Applied Sciences, 2017)
Â More advance, I t has studied in some papers that finding of first two moments of sample extremes of order statistics from discrete uniform distribution. In this paper, these moments are generalized. Also, for sample extremes of order statistics from discrete uniform distribution, moment generating functions are obtained.Â